Solventless curable composition, cured film produced using said composition, color filter including said cured film, and display device
By using curable units with substituted connection groups in the quantum dot curable composition, the dispersion and light efficiency of quantum dots in polar systems are solved, and the low viscosity and good inkjet printing performance of the composition are achieved without the use of solvents.
Patent Information
- Application Number
- JP2023545319
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-01-27
- Filing Date
- 2022-01-17
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2042-01-17
AI Technical Summary
The prior art encounters solvent limitations when introducing quantum dots into polar systems such as adhesives and curable units, resulting in limited dispersion and light efficiency of quantum dots in the curable composition, while solvent-based compositions are prone to problems such as dripping, clogging and single-layer thickness reduction during inkjet printing.
A solvent free curable composition containing curable units and quantum dots with a substituted linking group is employed, which is represented by chemical formula 1, has the effect of reducing viscosity and improving inkjet printing performance, and maintains stable storage stability and inkjet performance during prolonged stagnation without the use of solvent.
The good dispersion and light efficiency of quantum dots in the curable composition without using solvents is achieved, while maintaining the low viscosity of the composition and good inkjet printing performance, solving the problems of traditional solvent-based compositions in the inkjet printing process.
Smart Images

Figure 0007650992000018 
Figure 0007650992000019 
Figure 0007650992000020
Abstract
Description
[Technical field]
[0001] The present description relates to solventless curable compositions, cured films prepared using said compositions, color filters including said cured films, and display devices including said color filters. [Background technology]
[0002] In the case of general quantum dots, the solvents in which they can be dispersed are limited due to their hydrophobic surface properties, which makes it difficult to introduce them into polar systems such as binders and curable monomers.
[0003] For example, even in the case of quantum dot ink compositions that are being actively researched, in the early stages, they were still dispersed in solvents used in curable compositions that have relatively low polarity and high hydrophobicity. Therefore, it was difficult to include quantum dots at 20% by weight or more of the total composition, and the optical efficiency of the ink could not be increased beyond a certain level. Even if quantum dots were forcibly added and dispersed to increase the optical efficiency, the viscosity range for ink-jetting was exceeded, and processability could not be satisfied.
[0004] Also, in order to realize a viscosity range that allows ink-jetting, a method of lowering the ink solid content by including a solvent of 50% by weight or more relative to the total weight of the entire composition has been attempted. Although this method also provides a satisfactory result to a certain extent in terms of viscosity, it has the disadvantages of being difficult to apply to actual processes, such as problems such as nozzle drying due to solvent evaporation during ink-jetting, nozzle clogging, and a decrease in the single film thickness over time after ink-jetting, as well as severe thickness deviation after curing.
[0005] Therefore, the most suitable form of quantum dot ink for practical application is a solvent-free type, and it is considered that the current technology for applying quantum dots themselves to a solvent-based composition has already reached a certain limit.
[0006] In the reports to date, in the case of solvent-based compositions, quantum dots that have not been surface-modified, such as by ligand substitution, are contained in a content of about 20% to 25% by weight based on the total amount of the solvent-based composition, and therefore, due to the limitations of viscosity, it is difficult to increase the light efficiency and absorptivity. Meanwhile, as another improvement direction, a method of lowering the content of quantum dots and increasing the content of light diffusing agents (scatterers) has also been attempted, but this has also failed to improve the problems of sedimentation and low light efficiency. Summary of the Invention [Problem to be solved by the invention]
[0007] One embodiment is to provide a solventless curable composition comprising a curable monomer comprising a linking group having a substituent and a quantum dot.
[0008] Another embodiment provides a cured film produced using the solventless curable composition.
[0009] Yet another embodiment provides a color filter comprising the cured film.
[0010] Yet another embodiment is to provide a display device including the color filter. [Means for solving the problem]
[0011] One embodiment provides a solventless curable composition comprising quantum dots; and a curable monomer represented by Chemical Formula 1:
[0012] [ka]
[0013] In the above chemical formula 1, R 1 and R 2 each independently represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, L 1 teeth Single bond or an unsubstituted alkylene group having 1 to 20 carbon atoms, L 2 is a substituted alkylene group having 1 to 20 carbon atoms, L 3 is a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms.
[0014] The formula 1 can be represented by any one of the following formulas 1-1 to 1-3.
[0015] [ka]
[0016] In the above Chemical Formula 1-1 to Chemical Formula 1-3, R 1 and R 2 each independently represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, L 4 is an unsubstituted alkylene group having 1 to 20 carbon atoms, L 5 ~L 7 each independently represents a substituted alkylene group having 1 to 20 carbon atoms, L 8 ~L 10 are each independently a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, 8 ~L 10 At least one of these is necessarily a substituted alkylene group having 1 to 20 carbon atoms.
[0017] The curable monomer represented by the chemical formula 1 is 1.0×10 -4 torr~5.0×10 -2The vapor pressure may be as high as 1000 torr.
[0018] The curable monomer represented by Chemical Formula 1 may have a viscosity of 4 cps to 10 cps.
[0019] The curable monomer represented by Chemical Formula 1 can be represented by any one of Chemical Formulas 2 to 6 below.
[0020] [ka]
[0021] The solventless curable composition may have a viscosity of 20 cps to 40 cps.
[0022] The quantum dots may have a maximum fluorescent emission wavelength between 500 nm and 680 nm.
[0023] The solventless curable composition may contain 5% by weight to 60% by weight of the quantum dots and 40% by weight to 95% by weight of the curable monomer represented by Chemical Formula 1, based on the total amount of the solventless curable composition.
[0024] The solventless curable composition may further include a polymerization initiator, a light diffusing agent, or a combination thereof.
[0025] The light diffusing agent may include barium sulfate, calcium carbonate, titanium dioxide, zirconia, or combinations thereof.
[0026] The solventless curable composition may further include a polymerization inhibitor; malonic acid; 3-amino-1,2-propanediol; a silane coupling agent; a leveling agent; a fluorosurfactant; or a combination thereof.
[0027] Another embodiment provides a cured film produced using the solventless curable composition.
[0028] Yet another embodiment provides a color filter comprising the cured film.
[0029] Yet another embodiment provides a display device including the color filter.
[0030] Other specific aspects of the present invention are included in the following detailed description. Effect of the Invention
[0031] By modifying the structure of the curable monomer to include a linking group having a substituent, it is possible to provide a solventless curable composition that not only reduces the viscosity of the curable monomer and a composition containing the same, thereby improving the ink-jetting property, but also has excellent storage stability and ink ejection property even when the dwell time is long. [Brief description of the drawings]
[0032] [Figure 1] 1 is a photograph taken immediately after ink-jetting of the solventless curable composition according to Example 1. [Diagram 2] 1 is a photograph of the solventless curable composition of Example 1 being ink-jetted immediately after a 10-minute dwell time. [Diagram 3] 1 is a photograph of the solventless curable composition of Example 1 being ink-jetted immediately after a 30-minute dwell time. [Figure 4] 1 is a photograph of the solventless curable composition of Example 1 being ink-jetted immediately after a 60-minute dwell time. [Diagram 5] 1 is a photograph of the solventless curable composition of Example 1 being ink-jetted immediately after a 24-hour dwell time. [Figure 6] 1 is a photograph taken immediately after ink-jetting of the solventless curable composition according to Comparative Example 1. [Figure 7] 1 is a photograph of the solventless curable composition of Comparative Example 1 being ink-jetted immediately after a 10-minute dwell time. [Figure 8]1 is a photograph of the solventless curable composition of Comparative Example 1 being ink-jetted immediately after a 30-minute dwell time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0033] Hereinafter, embodiments of the present invention will be described in detail, but they are presented by way of example only and are not intended to limit the present invention, which is defined only by the scope of the claims that follow.
[0034] Unless otherwise specified in this specification, "alkyl group" means an alkyl group having 1 to 20 carbon atoms, "alkenyl group" means an alkenyl group having 2 to 20 carbon atoms, "cycloalkenyl group" means a cycloalkenyl group having 3 to 20 carbon atoms, "heterocycloalkenyl group" means a heterocycloalkenyl group having 3 to 20 carbon atoms, "aryl group" means an aryl group having 6 to 20 carbon atoms, "arylalkyl group" means an arylalkyl group having 6 to 20 carbon atoms, "alkylene group" means an alkylene group having 1 to 20 carbon atoms, "arylene group" means an arylene group having 6 to 20 carbon atoms, "alkylarylene group" means an alkylarylene group having 6 to 20 carbon atoms, "heteroarylene group" means a heteroarylene group having 3 to 20 carbon atoms, and "alkoxyylene group" means an alkoxyylene group having 1 to 20 carbon atoms.
[0035] Unless otherwise specified in this specification, "substituted" means that at least one hydrogen atom is replaced with a halogen atom (F, Cl, Br, I), a hydroxyl group, an alkoxy group having 1 to 20 carbon atoms, a nitro group, a cyano group, an amine group, an imino group, an azide group, an amidino group, a hydrazino group, a hydrazono group, a carbonyl group, a carbamoyl group, a thiol group, an ester group, an ether group, a carboxyl group or a salt thereof, a sulfonic acid group or a salt thereof, a phosphoric acid group or a salt thereof, an alkyl group having 1 to 20 carbon atoms, a carbon atom, a carboxylic acid group ... It means that the alkyl group is substituted with an alkenyl group having 2 to 20 carbon atoms, an alkynyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, a cycloalkenyl group having 3 to 20 carbon atoms, a cycloalkynyl group having 3 to 20 carbon atoms, a heterocycloalkyl group having 2 to 20 carbon atoms, a heterocycloalkenyl group having 2 to 20 carbon atoms, a heterocycloalkynyl group having 2 to 20 carbon atoms, a heteroaryl group having 3 to 20 carbon atoms, or a combination thereof.
[0036] In addition, unless otherwise specified in this specification, "hetero" means that at least one heteroatom selected from the group consisting of N, O, S and P is included in the chemical formula.
[0037] In addition, unless otherwise specified in this specification, "(meth)acrylate" means that both "acrylate" and "methacrylate" are possible, and "(meth)acrylic acid" means that both "acrylic acid" and "methacrylic acid" are possible.
[0038] Unless otherwise specified herein, "combination" means blending or copolymerization.
[0039] Unless otherwise defined in the chemical formulas herein, when no chemical bond is drawn at a position where a chemical bond should be drawn, it means that a hydrogen atom is bonded to said position.
[0040] Also, unless otherwise specified in this specification, "*" means a moiety connected to the same or different atom or chemical formula.
[0041] The present invention relates to a curable composition for a color filter applied to a display device, and more specifically, to a solventless curable ink composition containing quantum dots, which have recently been established as a new technology in the display field.
[0042] The quantum dot-containing photosensitive ink composition used in quantum dot displays is generally composed of basic components such as curable monomers, binder resins, initiators, solvents, and additives, and contains quantum dots and light diffusing agents to produce color characteristics. The quantum dots have the function of converting the blue light incident on the single layer into red light and green light after the single layer is formed.
[0043] However, in the case of a quantum dot-containing photosensitive ink composition containing a solvent, problems such as nozzle drying due to solvent evaporation during ink-jetting, nozzle clogging, and single layer reduction over time after ink-jetting, as well as severe thickness deviation after curing, make it difficult to apply to actual processes. Therefore, recently, research into a solventless quantum dot-containing curable ink composition that does not use any solvent at all, i.e., a solventless type, is being actively conducted.
[0044] The solventless quantum dot-containing curable ink composition contains a polyfunctional monomer that disperses the quantum dots well and allows the matrix to be well formed by UV curing or thermal curing. Among them, HDDA (1,6-hexanediol diacrylate) is widely used, and this monomer has a viscosity of about 6.2 cps, and when this monomer is made into a curable ink composition, the viscosity becomes about 26.3 cps. In order to apply a curable ink composition having such a relatively high viscosity to a process, the head temperature must be increased during ink-jetting to reduce the viscosity of the ink composition, and then ink-jetting must be performed. However, even in this case, issues such as nozzle clogging at the head nozzle and poor landing occur due to the increase in the head temperature.
[0045] Therefore, the present inventors have developed a solventless curable composition that not only disperses quantum dots well like existing monomers such as HDDA and forms a matrix well by UV curing or heat curing, but also minimizes the decrease in quantum efficiency of quantum dots even after exposure and heat processes, and further maintains storage stability and ink ejection properties even during long dwell times.
[0046] Each component constituting the solventless curable composition will be specifically described below.
[0047] Curable Monomer The curable monomer included in the solventless curable composition according to an embodiment is a monomer having carbon-carbon double bonds at both ends, and is specifically represented by the following Chemical Formula 1.
[0048] [ka]
[0049] In the above chemical formula 1, R 1 and R 2 each independently represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, L 1 teeth Single bond or an unsubstituted alkylene group having 1 to 20 carbon atoms, L 2 is a substituted alkylene group having 1 to 20 carbon atoms, L 3 is a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms.
[0050] The curable monomer represented by Chemical Formula 1 necessarily contains a substituent such as an alkyl group in the linking group between the (meth)acrylate groups at both ends. This not only reduces the viscosity of the curable monomer represented by Chemical Formula 1 itself, but also reduces the viscosity of a solventless curable composition containing the same, greatly improving the ink-jetting properties, and further contributes to minimizing the decrease in quantum efficiency of quantum dots, which will be described later, even after exposure and heat processes.
[0051] In addition, by including the curable monomer represented by Chemical Formula 1, the solventless curable composition according to an embodiment has very little change in viscosity due to storage time of the composition even at a temperature higher than room temperature, and has excellent storage stability. Furthermore, even if the stagnation time during the ink-jetting process becomes long, the ink ejection property can be maintained without being decreased.
[0052] For example, the formula 1 may be represented by any one of the following formulas 1-1 to 1-3, but is not limited thereto.
[0053] [ka]
[0054] In the above Chemical Formula 1-1 to Chemical Formula 1-3, R 1 and R 2 each independently represents a hydrogen atom or a substituted or unsubstituted alkyl group having 1 to 10 carbon atoms, L 4 is an unsubstituted alkylene group having 1 to 20 carbon atoms, L 5 ~L 7 each independently represents a substituted alkylene group having 1 to 20 carbon atoms, L 8 ~L 10 are each independently a substituted or unsubstituted alkylene group having 1 to 20 carbon atoms, 8 ~L 10At least one of these is necessarily a substituted alkylene group having 1 to 20 carbon atoms.
[0055] For example, the curable monomer represented by the above formula 1 is 1.0×10 -4 torr~5.0×10 -2 The vapor pressure may be as high as 1000 torr.
[0056] For example, the curable monomer represented by Chemical Formula 1 may have a viscosity of 4 cps to 10 cps. In this specification, the viscosity and vapor pressure are values measured at room temperature, 25°C.
[0057] For example, the curable monomer represented by Formula 1 may be represented by any one of Formulas 2 to 6 below, but is not limited thereto.
[0058] [ka]
[0059] For example, the solventless curable composition can have a viscosity of 20 cps to 40 cps.
[0060] The curable monomer represented by Chemical Formula 1 may be included in the solventless curable composition in an amount of 40% by weight to 95% by weight, for example, 45% by weight to 90% by weight, for example, 45% by weight to 85% by weight, for example, 50% by weight to 80% by weight, based on the total amount of the solventless curable composition. Only when the content of the curable monomer represented by Chemical Formula 1 is within the above range can a solventless curable composition having a viscosity suitable for ink-jetting be prepared, and the quantum dots in the prepared solventless curable composition can have excellent dispersibility, thereby improving optical properties.
[0061] For example, the curable monomer represented by Formula 1 may have a molecular weight of 180 g / mol to 1,000 g / mol. When the molecular weight of the curable monomer represented by Formula 1 is within this range, it may be advantageous for ink-jetting since it does not inhibit the optical properties of the quantum dots and does not increase the viscosity of the composition.
[0062] In addition, the solventless curable composition according to an embodiment may further include a monomer that is generally used in conventional thermosetting or photocurable compositions in addition to the curable monomer represented by Chemical Formula 1. For example, the monomer may further include an oxetane-based compound such as bis[1-ethyl(3-oxetanyl)]methyl ether.
[0063] Quantum dots The quantum dots contained in the solventless curable composition can absorb light in a wavelength range of 360 nm to 780 nm, for example, in a wavelength range of 400 nm to 780 nm, and emit fluorescence in a wavelength range of 500 nm to 700 nm, for example, in a range of 500 nm to 580 nm, or in a range of 600 nm to 680 nm. That is, the quantum dots have a maximum fluorescence emission wavelength (fluorescence λ ) in the range of 500 nm to 680 nm. em ).
[0064] The quantum dots may each independently have a full width at half maximum (FWHM) of 20 nm to 100 nm, for example, 20 nm to 50 nm. When the quantum dots have a full width at half maximum in the above range, the quantum dots have high color purity, which has the effect of improving color reproduction when used as a color material in a color filter.
[0065] The quantum dots may each independently be organic, inorganic, or a hybrid of organic and inorganic.
[0066] The quantum dots may each be independently composed of a core and a shell surrounding the core, and the core and shell may each independently have a structure such as a core made of II-IV group, III-V group, etc., a core / shell, a core / first shell / second shell, an alloy, an alloy / shell, etc., but are not limited thereto.
[0067] For example, the core may include, but is not limited to, at least one material selected from the group consisting of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, GaN, GaP, GaAs, InP, InAs, and alloys thereof, and the shell surrounding the core may include, but is not limited to, at least one material selected from the group consisting of CdSe, ZnSe, ZnS, ZnTe, CdTe, PbS, TiO, SrSe, HgSe, and alloys thereof.
[0068] In one embodiment, in response to the recent increase in interest in the environment worldwide and the tightening of regulations on toxic materials, an environmentally friendly non-cadmium-based luminescent material (InP / ZnS, InP / ZeSe / ZnS, etc.) is used instead of a luminescent material having a cadmium core, although the quantum efficiency is somewhat lower, but the present invention is not limited thereto.
[0069] In the case of quantum dots having a core / shell structure, the size (average particle size) of each of the entire quantum dots including the shell may be 1 nm to 15 nm, for example, 5 nm to 15 nm.
[0070] For example, the quantum dots may each independently include red quantum dots, green quantum dots, or a combination thereof. The red quantum dots may each independently have an average particle size of 10 nm to 15 nm. The green quantum dots may each independently have an average particle size of 5 nm to 8 nm.
[0071] Meanwhile, for the dispersion stability of the quantum dots, the solventless curable composition according to an embodiment may further include a dispersant to include the quantum dots in the form of a quantum dot dispersion. The dispersant helps the light conversion material such as quantum dots to be uniformly dispersed in the solventless curable composition, and may be any nonionic, anionic, or cationic dispersant. Specifically, polyalkylene glycol or its esters, polyoxyalkylene, polyhydric alcohol ester alkylene oxide adduct, alcohol alkylene oxide adduct, sulfonic acid ester, sulfonic acid salt, carboxylic acid ester, carboxylic acid salt, alkylamide alkylene oxide adduct, alkylamine, etc. may be used alone or in combination of two or more. The dispersant may be used in an amount of 0.1% by weight to 100% by weight, for example, 10% by weight to 20% by weight, based on the solid content of the light conversion material such as quantum dots.
[0072] The quantum dots may be surface-modified with a conventional quantum dot surface-modifying substance (eg, a thiol-based compound, etc.), or may not be surface-modified.
[0073] The quantum dots may be contained in an amount of 5% by weight to 60% by weight, for example, 10% by weight to 60% by weight, for example, 20% by weight to 50% by weight, for example, 30% by weight to 50% by weight, based on the total amount of the solventless curable composition. When the quantum dots (e.g., quantum dot dispersion) are contained within the above range, the photoconversion rate is excellent, and the pattern characteristics and development characteristics are not hindered, resulting in excellent processability.
[0074] Polymerization initiator The solventless curable composition according to an embodiment may further include a polymerization initiator, for example, a photoinitiator, a thermal polymerization initiator, or a combination thereof.
[0075] The photopolymerization initiator is an initiator commonly used in photosensitive resin compositions, and examples thereof include, but are not limited to, acetophenone-based compounds, benzophenone-based compounds, thioxanthone-based compounds, benzoin-based compounds, triazine-based compounds, oxime-based compounds, and aminoketone-based compounds.
[0076] Examples of the acetophenone-based compounds include 2,2'-diethoxyacetophenone, 2,2'-dibutoxyacetophenone, 2-hydroxy-2-methylpropiophenone, pt-butyltrichloroacetophenone, pt-butyldichloroacetophenone, 4-chloroacetophenone, 2,2'-dichloro-4-phenoxyacetophenone, 2-methyl-1-(4-(methylthio)phenyl)-2-morpholinopropan-1-one, and 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one.
[0077] Examples of the benzophenone-based compounds include benzophenone, benzoylbenzoic acid, methyl benzoylbenzoate, 4-phenylbenzophenone, hydroxybenzophenone, acrylated benzophenone, 4,4'-bis(dimethylamino)benzophenone, 4,4'-bis(diethylamino)benzophenone, 4,4'-dimethylaminobenzophenone, 4,4'-dichlorobenzophenone, and 3,3'-dimethyl-2-methoxybenzophenone.
[0078] Examples of the thioxanthone compounds include thioxanthone, 2-methylthioxanthone, isopropylthioxanthone, 2,4-diethylthioxanthone, 2,4-diisopropylthioxanthone, and 2-chlorothioxanthone.
[0079] Examples of the benzoin-based compounds include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and benzyl dimethyl ketal.
[0080] Examples of the triazine-based compound include 2,4,6-trichloro-s-triazine, 2-phenyl-4,6-bis(trichloromethyl)-s-triazine, 2-(3',4'-dimethoxystyryl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4'-methoxynaphthyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-methoxyphenyl)-4,6-bis(trichloromethyl)-s-triazine, 2-(p-tolyl)-4,6-bis(trichloromethyl)-s-triazine, azine, 2-biphenyl-4,6-bis(trichloromethyl)-s-triazine, bis(trichloromethyl)-6-styryl-s-triazine, 2-(naphth-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-(4-methoxynaphth-1-yl)-4,6-bis(trichloromethyl)-s-triazine, 2-4-bis(trichloromethyl)-6-piperonyl-s-triazine, 2-4-bis(trichloromethyl)-6-(4-methoxystyryl)-s-triazine, and the like.
[0081] Examples of the oxime-based compound include O-acyloxime-based compounds, 2-(O-benzoyloxime)-1-[4-(phenylthio)phenyl]-1,2-octanedione, 1-(O-acetyloxime)-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone, and O-ethoxycarbonyl-α-oxyamino-1-phenylpropan-1-one. Specific examples of the O-acyloxime compounds include 1,2-octanedione, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-yl-phenyl)-butan-1-one, 1-(4-phenylsulfanylphenyl)-butan-1,2-dione-2-oxime-O-benzoate, 1-(4-phenylsulfanylphenyl)-octane-1,2-dione-2-oxime-O-benzoate, 1-(4-phenylsulfanylphenyl)-octan-1-one oxime-O-acetate, and 1-(4-phenylsulfanylphenyl)-butan-1-one oxime-O-acetate.
[0082] Examples of the aminoketone compounds include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butanone-1.
[0083] As the photopolymerization initiator, in addition to the above compounds, carbazole-based compounds, diketone compounds, sulfonium borate-based compounds, diazo-based compounds, imidazole-based compounds, biimidazole-based compounds, etc. can be used.
[0084] The photoinitiator may be used in conjunction with a photosensitizer, which absorbs light, becomes excited, and then transfers its energy to initiate a chemical reaction.
[0085] Examples of the photosensitizer include tetraethylene glycol bis-3-mercaptopropionate, pentaerythritol tetrakis-3-mercaptopropionate, and dipentaerythritol tetrakis-3-mercaptopropionate.
[0086] Examples of the thermal polymerization initiator include peroxides, specifically benzoyl peroxide, dibenzoyl peroxide, lauryl peroxide, dilauryl peroxide, di-tert-butyl peroxide, cyclohexane peroxide, methyl ethyl ketone peroxide, hydroperoxides (e.g., tert-butyl hydroperoxide, cumene hydroperoxide), dicyclohexyl peroxydicarbonate, 2,2-azo-bis(isobutyronitrile), t-butyl perbenzoate, and 2,2'-azobis-2-methylpropionitrile, but are not limited thereto. Any of those widely known in the art may be used.
[0087] The polymerization initiator may be included in an amount of 0.1% by weight to 5% by weight, for example, 1% by weight to 4% by weight, based on the total amount of the solventless curable composition. When the polymerization initiator is included within the above range, curing occurs sufficiently during exposure or thermal curing, so that excellent reliability can be obtained, and a decrease in transmittance due to unreacted initiator can be prevented, thereby preventing a decrease in the optical properties of quantum dots.
[0088] Light Diffuser The solventless curable composition according to an embodiment may further include a light diffusing agent.
[0089] For example, the light diffusing agent can include barium sulfate (BaSO4), calcium carbonate (CaCO3), titanium dioxide (TiO2), zirconia (ZrO2), or combinations thereof.
[0090] The light diffusing agent reflects light that is not absorbed by the quantum dots and allows the quantum dots to absorb the reflected light again, i.e., the light diffusing agent increases the amount of light absorbed by the quantum dots, thereby increasing the light conversion efficiency of the curable composition.
[0091] The light diffusing agent has an average particle size (D 50 ) may be 150 nm to 250 nm, specifically, 180 nm to 230 nm. When the average particle size of the light diffusing agent is within the above range, a better light diffusing effect can be obtained, and the light conversion efficiency can be increased.
[0092] The light diffusing agent may be contained in an amount of 1 wt% to 20 wt%, for example, 5 wt% to 10 wt%, based on the total amount of the solventless curable composition. If the light diffusing agent is contained in an amount of less than 1 wt% based on the total amount of the solventless curable composition, it is difficult to expect an effect of improving light conversion efficiency by using the light diffusing agent, and if it is contained in an amount of more than 20 wt%, a problem of quantum dot sedimentation may occur.
[0093] Other Additives In order to improve the stability and dispersibility of the quantum dots, the solventless curable composition according to an embodiment may further include a polymerization inhibitor.
[0094] The polymerization inhibitor may include, but is not necessarily limited to, a hydroquinone-based compound, a catechol-based compound, or a combination thereof. When the solventless curable composition according to an embodiment further includes the hydroquinone-based compound, the catechol-based compound, or a combination thereof, room temperature crosslinking can be prevented during exposure after printing (coating) of the solventless curable composition.
[0095] For example, the hydroquinone-based compound, the catechol-based compound, or a combination thereof may include, but is not necessarily limited to, hydroquinone, methylhydroquinone, methoxyhydroquinone, t-butylhydroquinone, 2,5-di-t-butylhydroquinone, 2,5-bis(1,1-dimethylbutyl)hydroquinone, 2,5-bis(1,1,3,3-tetramethylbutyl)hydroquinone, catechol, t-butylcatechol, 4-methoxyphenol, pyrogallol, 2,6-di-t-butyl-4-methylphenol, 2-naphthol, tris(N-hydroxy-N-nitrosophenylaminato-O,O')aluminium, or a combination thereof.
[0096] The hydroquinone-based compound, the catechol-based compound, or a combination thereof can be used in the form of a dispersion, and the polymerization inhibitor in the form of a dispersion may be contained in an amount of 0.001% by weight to 3% by weight, for example, 0.1% by weight to 2% by weight, based on the total amount of the solventless curable composition. When the polymerization inhibitor is contained within the above range, the room temperature aging problem can be solved, and at the same time, the sensitivity reduction and surface peeling phenomenon can be prevented.
[0097] In addition, the solventless curable composition according to an embodiment may further include malonic acid; 3-amino-1,2-propanediol; a silane coupling agent; a leveling agent; a fluorine-based surfactant; or a combination thereof in order to improve heat resistance and reliability.
[0098] For example, the solventless curable composition according to an embodiment may further include a silane coupling agent having a reactive substituent such as a vinyl group, a carboxyl group, a methacryloxy group, an isocyanate group, or an epoxy group in order to improve adhesion to a substrate.
[0099] Examples of the silane coupling agent include trimethoxysilylbenzoic acid, gamma methacryloxypropyltrimethoxysilane, vinyltriacetoxysilane, vinyltrimethoxysilane, gamma isocyanatepropyltriethoxysilane, gamma glycidoxypropyltrimethoxysilane, and beta epoxycyclohexylethyltrimethoxysilane. These can be used alone or in combination of two or more.
[0100] The silane coupling agent may be contained in an amount of 0.01 to 10 parts by weight relative to 100 parts by weight of the solventless curable composition. When the silane coupling agent is contained within the above range, the composition has excellent adhesion, storage stability, and the like.
[0101] In addition, the solventless curable composition may further include a surfactant, for example, a fluorine-based surfactant, for improving coating properties and preventing the generation of defects, i.e., improving leveling performance, if necessary.
[0102] The fluorosurfactant may have a low weight average molecular weight of 4,000 g / mol to 10,000 g / mol, specifically, a weight average molecular weight of 6,000 g / mol to 10,000 g / mol. The fluorosurfactant may have a surface tension of 18 mN / m to 23 mN / m (measured in a 0.1% propylene glycol monomethyl ether acetate (PGMEA) solution). When the weight average molecular weight and surface tension of the fluorosurfactant are within the above ranges, the leveling performance can be further improved, the occurrence of stains during high speed coating can be prevented, and there is little bubble generation and film defects, providing excellent properties to slit coating, which is a high speed coating method.
[0103] Examples of the fluorine-based surfactant include BM-1000 (registered trademark) and BM-1100 (registered trademark) manufactured by BM Chemie; Megafac F 142D (registered trademark), F 172 (registered trademark), F 173 (registered trademark), F 174 (registered trademark) manufactured by Dainippon Ink and Chemicals, Inc.; 183 (registered trademark), etc.; Fluorad FC-135 (registered trademark), FC-170C (registered trademark), FC-430 (registered trademark), FC-431 (registered trademark), etc., from Sumitomo 3M Limited; Surflon S-112 (registered trademark), S-113 (registered trademark), S-131 (registered trademark), S-141 (registered trademark), S-145 (registered trademark), etc., from Asahi Glass Co., Ltd.; SH-28PA (registered trademark), S-190 (registered trademark), S-193 (registered trademark), SZ-6032 (registered trademark), SF-8428 (registered trademark), etc., from Toray Silicon Co., Ltd.; and fluorine-based surfactants commercially available under the names F-482, F-484, F-478, F-554, etc., from DIC Corporation, can be used.
[0104] In addition, the solventless curable composition according to an embodiment may use a silicone surfactant together with the fluorosurfactant. Specific examples of the silicone surfactant include, but are not limited to, TSF400, TSF401, TSF410, and TSF4440 manufactured by Toshiba Silicon Corporation.
[0105] The surfactant including the fluorine-based surfactant may be included in an amount of 0.01 to 5 parts by weight, for example, 0.1 to 2 parts by weight, based on 100 parts by weight of the solventless curable composition. When the surfactant is included in the above range, the phenomenon of foreign matter being generated in the sprayed composition is reduced.
[0106] In addition, the solventless curable composition according to an embodiment may further contain a certain amount of other additives, such as an antioxidant, within a range that does not impair physical properties.
[0107] Another embodiment provides a cured film produced using the solventless curable composition, and a color filter including the cured film.
[0108] One of the methods for preparing the cured film includes the steps of: applying the solventless curable composition onto a substrate by an inkjet spraying method to form a pattern (S1); and curing the pattern (S2).
[0109] (S1) Pattern formation stage The solventless curable composition is preferably applied to a substrate in a thickness of 0.5 to 20 μm by an inkjet dispersion method. The inkjet spraying can form a pattern by spraying only a single color from each nozzle and repeatedly spraying according to the number of colors required, or can form a pattern by simultaneously spraying the number of colors required through each inkjet nozzle to reduce the number of processes.
[0110] (S2) Hardening stage The obtained pattern is cured to obtain pixels. At this time, the curing method can be a thermal curing process or a photocuring process. The thermal curing process is preferably performed by heating at a temperature of 100° C. or more, more preferably at 100° C. to 300° C., and even more preferably at 160° C. to 250° C. The photocuring process is performed by irradiating actinic rays such as UV rays of 190 nm to 450 nm, for example, 200 nm to 500 nm. The light source used for irradiation can be a low pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a metal halide lamp, an argon gas laser, or the like, and X-rays, electron beams, etc. can also be used in some cases.
[0111] Another method for producing the cured film is to produce a cured film by using the solventless curable composition by a lithography method, and the production method is as follows.
[0112] (1) Coating and film formation stage The solventless curable composition is applied to a substrate that has been subjected to a predetermined pretreatment in a desired thickness, for example, 2 μm to 10 μm, using a method such as spin or slit coating, roll coating, screen printing, or applicator, and then heated at a temperature of 70° C. to 90° C. for 1 minute to 10 minutes to remove the solvent, thereby forming a coating film.
[0113] (2) Exposure stage The coating film thus obtained is exposed to a mask having a predetermined shape for forming a necessary pattern, and then is irradiated with actinic radiation such as UV light having a wavelength of 190 nm to 450 nm, for example, 200 nm to 500 nm. As a light source used for the irradiation, a low pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a metal halide lamp, an argon gas laser, or the like can be used, and in some cases, X-rays, electron beams, or the like can also be used.
[0114] The exposure dose varies depending on the type and amount of each component of the curable composition and the thickness of the dried film. For example, when a high-pressure mercury lamp is used, the exposure dose is 500 mJ / cm 2Below is the result (based on a 365 nm sensor).
[0115] (3) Development stage Following the exposure step, an alkaline aqueous solution is used as a developer to dissolve and remove unnecessary portions, leaving only the exposed portions to form an image pattern. That is, when developed with an alkaline developer, the unexposed portions are dissolved to form an image color filter pattern.
[0116] (4) Post-processing stage The image pattern obtained by the development can be cured by heating again or by exposure to actinic radiation in order to obtain a pattern excellent in heat resistance, light resistance, adhesion, crack resistance, chemical resistance, high strength, storage stability, and the like.
[0117] Yet another embodiment provides a display device, such as an LCD, LED, or OLED display device, including the color filter.
[0118] Hereinafter, preferred embodiments of the present invention will be described, however, the following embodiment is merely a preferred embodiment of the present invention and the present invention is not limited to the following embodiment. EXAMPLES
[0119] (Synthesis of curable monomer) Synthesis Example 1 In a round-bottom flask, 10 g of 3-methyl-1,5-pentanediol is dissolved in 100 g of cyclohexane. Then, 3.4 g of acrylic acid and 2.4 g of methane sulfonic acid are added and reacted at 100°C for 20 hours to produce a curable monomer (molecular weight: 226 g / mol) (vapor pressure at 25°C: 2.0 x 10) represented by the following chemical formula 2. -3 mmHg) was synthesized.
[0120] [ka]
[0121] Synthesis Example 2 In a round-bottom flask, 10 g of 2,3-butanediol was dissolved in 100 g of cyclohexane. Then, 17.6 g of acrylic acid and 3.2 g of methane sulfonic acid were added and reacted at 100°C for 20 hours to synthesize a curable monomer (molecular weight: 198 g / mol) represented by the following chemical formula 3.
[0122] [ka]
[0123] Synthesis Example 3 In a round-bottom flask, 10 g of 1,2-pentanediol was dissolved in 100 g of cyclohexane. Then, 15.2 g of acrylic acid and 2.8 g of methane sulfonic acid were added and reacted at 100°C for 20 hours to synthesize a curable monomer (molecular weight: 212 g / mol) represented by the following chemical formula 4.
[0124] [ka]
[0125] Synthesis Example 4 In a round-bottom flask, 10 g of 1,2-hexanediol was dissolved in 100 g of cyclohexane. Then, 13.4 g of acrylic acid and 2.4 g of methane sulfonic acid were added and reacted at 100°C for 20 hours to synthesize a curable monomer (molecular weight: 226 g / mol) represented by the following chemical formula 5.
[0126] [ka]
[0127] Synthesis Example 5 In a round-bottom flask, 10 g of 3,4-heptanediol was dissolved in 100 g of cyclohexane. Then, 12.0 g of acrylic acid and 2.2 g of methane sulfonic acid were added and reacted at 100°C for 20 hours to synthesize a curable monomer (weight average molecular weight: 240 g / mol) represented by the following chemical formula 6.
[0128] [ka]
[0129] Evaluation 1: Viscosity measurement of curable monomer The curable monomer of Synthesis Example 1 and HDDA (1,6-hexanediol diacrylate) (MIRAMER M200, Miwon Specialty Chemical Co., Ltd.) (vapor pressure at 25°C: 1.0 × 10 -3 The initial viscosity was measured at 25° C. using a viscometer (Thermo Scientific, HAAKE Rheostress 6000, C60 / 1 spindle, shear rate 600) against the viscosity of the mixture (Hg / mmHg), and the results are shown in Table 1 below.
[0130] [Table 1]
[0131] As shown in Table 1 above, it can be seen that the curable monomer of Synthesis Example 1, which contains a linking group having a substituent, has a lower viscosity than HDDA, which contains a linking group without a substituent.
[0132] (Fabrication of surface-modified quantum dots) Manufacturing Example Place a magnetic bar in a three-neck round-bottom flask and add the green quantum dot dispersion solution (InP / ZnSe / ZnS, Hansol Chemical; quantum dot solids content 23% by weight). Then add the compound (ligand) represented by the following chemical formula Q and stir at 80°C in a nitrogen atmosphere. After the reaction is complete, cool to room temperature (23°C) and then add the quantum dot reaction solution to cyclohexane to remove the precipitate. The precipitate and cyclohexane are separated using centrifugation and the precipitate is thoroughly dried in a vacuum oven for one day to obtain surface-modified quantum dots.
[0133] (*Synthesis of the compound represented by the chemical formula Q: 100g of PH-4 (Hannong Chemical) is placed in a two-necked round-bottom flask and thoroughly dissolved in 300mL of THF. At 0°C, 15.4g of NaOH and 100mL of water are added and thoroughly dissolved until a clear solution is obtained. A solution of 73g of para-toluene sulfonic chloride dissolved in 100mL of THF is gradually added at 0°C. The addition is continued for 1 hour, and then the solution is stirred at room temperature for 12 hours. After the reaction is complete, an excess of methylene chloride is added and stirred, and then a saturated solution of NaHCO3 is added and extracted, titrated, and the water is removed. After the solvent is removed, the solution is dried in a dry oven for 24 hours. 50g of the obtained dried product is placed in a two-necked round-bottom flask and thoroughly stirred in 300mL of ethanol. Then, 27g of Thiourea is added and dispersed, and the solution is refluxed at 80°C for 12 hours. Then, an aqueous solution of 4.4g of NaOH dissolved in 20mL of water is added and stirred for an additional 5 hours, while removing the excess of methylene chloride. After adding chloride and stirring, add hydrochloric acid solution and perform extraction, titration, water removal, and solvent removal in sequence. Dry in a vacuum oven for 24 hours to obtain the compound represented by the following chemical formula Q.
[0134] [ka]
[0135] (Production of solvent-free curable composition) Example 1 The green quantum dot solid content of the Preparation Example was mixed with the curable monomer of Synthesis Example 1 in the same weight ratio and stirred for 12 hours to obtain a quantum dot dispersion liquid.
[0136] The quantum dot dispersion is diluted by adding the curable monomer of Synthesis Example 1, and a polymerization inhibitor (methylhydroquinone, TOKYO CHEMICAL) is added and stirred for 5 minutes. Then, a photoinitiator (TPO-L, Polynetron) is added, followed by a light diffusing agent (rutile type TiO2; having a particle size of 180 nm). The prepared solution is then stirred for 1 hour to produce a solventless curable composition. The composition of the solventless curable composition is as shown in Table 2 below. (In the case of Example 1, 40 g of green quantum dot solids are mixed with 40 g of the curable monomer of Synthesis Example 1 to produce a quantum dot dispersion, and then 10.5 g of the curable monomer of Synthesis Example 1 and 0.5 g of the polymerization inhibitor are added to the quantum dot dispersion and stirred for 5 minutes, and then 3 g of the photoinitiator and 4 g of the light diffusing agent are added and stirred to produce a solventless curable composition.)
[0137] [Table 2]
[0138] Example 2 The same procedure as in Example 1 was repeated, except that the curable monomer obtained in Synthesis Example 2 was used instead of the curable monomer obtained in Synthesis Example 1.
[0139] Example 3 The same procedure as in Example 1 was repeated, except that the curable monomer obtained in Synthesis Example 3 was used instead of the curable monomer obtained in Synthesis Example 1.
[0140] Example 4 The same procedure as in Example 1 was repeated, except that the curable monomer obtained in Synthesis Example 4 was used instead of the curable monomer obtained in Synthesis Example 1.
[0141] Example 5 The same procedure as in Example 1 was repeated, except that the curable monomer obtained in Synthesis Example 5 was used instead of the curable monomer obtained in Synthesis Example 1.
[0142] Comparative Example 1 The same procedure as in Example 1 was repeated, except that HDDA (1,6-hexanediol diacrylate) was used instead of the curable monomer obtained in Synthesis Example 1.
[0143] Evaluation 2: Optical characteristics evaluation The solventless curable compositions prepared in Example 1 and Comparative Example 1 were each coated on a yellow photoresist (YPR) to a thickness of 15 μm using a spin coater (Mikasa, Opticoat MS-A150, 830 rpm, 5 seconds) and exposed to 5000 mJ (83°C, 10 seconds) using a 395 nm UV exposure device under a nitrogen atmosphere. Then, a 2 cm x 2 cm single-film specimen was loaded into an integrating sphere device (QE-2100, Otsuka Electronics) to measure the external quantum efficiency of the quantum dots (external quantum efficiency after exposure). Then, the loaded single-film specimen was dried (heat process) for 30 minutes in a drying oven in a nitrogen atmosphere at 180°C, and the external quantum efficiency of the quantum dots (external quantum efficiency after heat process) was measured again, and the results are shown in Table 3 below.
[0144] [Table 3]
[0145] From Table 3 above, it can be seen that both the solventless curable composition according to Example 1 and the solventless curable composition according to Comparative Example 1 can minimize the decrease in quantum efficiency of quantum dots.
[0146] Evaluation 3: Storage stability (40℃) evaluation In order to evaluate the storage stability of the solventless curable compositions prepared in Examples 1 to 5 and Comparative Example 1, the initial viscosity value of each composition at 40°C and the viscosity value after 14 days (while maintaining the same temperature conditions) were measured using a viscometer (Brookfield DV-II, RV-2 spindle, 23 rpm), and the difference between the initial viscosity value and the viscosity value after 14 days is shown in Table 4 below.
[0147] [Table 4]
[0148] From Table 4 above, it can be seen that the solventless curable composition according to one embodiment has superior storage stability compared to the solventless curable composition according to Comparative Example 1.
[0149] Evaluation 4: Ink-jetting characteristics evaluation by dwell time In order to evaluate the ink-jetting properties of the solventless curable compositions prepared in Examples 1 to 5 and Comparative Example 1, each composition was ink-jetted with different dwell times, and then photographs were taken to evaluate the ink ejection properties. The results are shown in Figs. 1 to 8.
[0150] From Figs. 1 to 8, it can be seen that the solventless curable composition according to one embodiment maintains its dischargeability even with a long retention time, whereas the solventless curable composition according to Comparative Example 1 exhibits reduced dischargeability despite a short retention time.
[0151] The present invention is not limited to the above-mentioned embodiments, and can be manufactured in various different forms, and a person having ordinary skill in the art to which the present invention pertains can understand that the present invention can be embodied in other specific forms without changing the technical idea or essential features of the present invention. Therefore, it should be understood that the above-described embodiments are illustrative in all respects and are not limiting.
Claims
1. Quantum dots; and At least one selected from the group consisting of a curable monomer represented by the following chemical formula 1-2, a curable monomer represented by the following chemical formula 4, and a curable monomer represented by the following chemical formula 5: A solventless curable composition comprising: 【Chemistry 1】 In the above chemical formula 1-2, R 1 and R 2 each independently represents a hydrogen atom, a halogen atom (F, Cl, Br, I), a hydroxyl group, an alkoxy group having 1 to 20 carbon atoms, a nitro group, a cyano group, an amine group, an imino group, an azide group, an amidino group, a hydrazino group, a hydrazono group, a carbonyl group, a carbamoyl group, a thiol group, an ester group, an ether group, a carboxyl group or a salt thereof, a sulfonic acid group or a salt thereof, a phosphoric acid group or a salt thereof, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a carbon atom, an alkyl group having 1 to 10 carbon atoms which is unsubstituted or substituted with an alkynyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, a cycloalkenyl group having 3 to 20 carbon atoms, a cycloalkynyl group having 3 to 20 carbon atoms, a heterocycloalkyl group having 2 to 20 carbon atoms, a heterocycloalkenyl group having 2 to 20 carbon atoms, a heterocycloalkynyl group having 2 to 20 carbon atoms, a heteroaryl group having 3 to 20 carbon atoms, or a combination thereof; L 6 and L 7 each independently represents a halogen atom (F, Cl, Br, I), a hydroxy group, an alkoxy group having 1 to 20 carbon atoms, a nitro group, a cyano group, an amine group, an imino group, an azide group, an amidino group, a hydrazino group, a hydrazono group, a carbonyl group, a carbamoyl group, a thiol group, an ester group, an ether group, a carboxyl group or a salt thereof, a sulfonic acid group or a salt thereof, a phosphoric acid group or a salt thereof, an alkyl group having 1 to 20 carbon atoms, an alkenyl group having 2 to 20 carbon atoms, a carbon and alkylene groups having 1 to 20 carbon atoms substituted with a substituent such as an alkynyl group having 2 to 20 carbon atoms, an aryl group having 6 to 20 carbon atoms, a cycloalkyl group having 3 to 20 carbon atoms, a cycloalkenyl group having 3 to 20 carbon atoms, a cycloalkynyl group having 3 to 20 carbon atoms, a heterocycloalkyl group having 2 to 20 carbon atoms, a heterocycloalkenyl group having 2 to 20 carbon atoms, a heterocycloalkynyl group having 2 to 20 carbon atoms, a heteroaryl group having 3 to 20 carbon atoms, or a combination thereof.
2. At least one selected from the group consisting of the curable monomer represented by Chemical Formula 1-2, the curable monomer represented by Chemical Formula 4, and the curable monomer represented by Chemical Formula 5 is 1.0 × 10 -4 torr~5.0×10 -2 2. The solventless curable composition of claim 1 having a vapor pressure of about 1000 torr.
3. The solventless curable composition according to claim 2, wherein at least one selected from the group consisting of the curable monomer represented by the chemical formula 1-2, the curable monomer represented by the chemical formula 4, and the curable monomer represented by the chemical formula 5 has a viscosity of 4 cps to 10 cps.
4. The solventless curable composition according to claim 1, wherein the solventless curable composition has a viscosity of 20 cps to 40 cps.
5. The solventless curable composition of claim 1, wherein the quantum dots have a maximum fluorescent emission wavelength in the range of 500 nm to 680 nm.
6. The solvent-free curable composition contains, relative to the total amount of the solvent-free curable composition, 5% to 60% by weight of the quantum dots; and 40% by weight to 95% by weight of at least one selected from the group consisting of the curable monomer represented by the chemical formula 1-2, the curable monomer represented by the chemical formula 4, and the curable monomer represented by the chemical formula 5 The solventless curable composition of claim 1 , comprising:
7. The solventless curable composition of claim 1 , further comprising a polymerization initiator, a light diffusing agent, or a combination thereof.
8. 8. The solventless curable composition of claim 7, wherein the light diffusing agent comprises barium sulfate, calcium carbonate, titanium dioxide, zirconia, or a combination thereof.
9. The solventless curable composition according to claim 1, further comprising: a polymerization inhibitor; malonic acid; 3-amino-1,2-propanediol; a silane-based coupling agent; a leveling agent; a fluorosurfactant; or a combination thereof.
10. A cured film produced using the solventless curable composition according to any one of claims 1 to 9.
11. A color filter comprising the cured film according to claim 10.
12. A display device comprising the color filter of claim 11.
Citation Information
Patent Citations
Ink composition, photoconversion layer and color filter
JP2019112516A
Ink composition, photoconversion layer and color filter
JP2020015895A
Quantum dot, curable composition containing the same, cured film produced using curable composition, color filter including cured film, display device, and method of fabricating cured film
JP2020118971A
Non-solvent type curable composition, cured film produced using the same, color filter including the cured film, display device, and method of manufacturing the cured film
JP2020126234A
Acid stabilization of quantum dot-resin concentrates and premixes
JP2020522591A